Criminal Law Policy Regarding Criminal Sanctions In Law Number 4 Of 2009 As Amended By Law Number 3 Of 2020 Concerning Mineral And Coal Mining And Law Number 32 Of 2009 Concerning Environmental Protection And Management - Dian Anggraini (Jurnal Multidisiplin Sahombu, 2024)
This study examines the legal implications related to criminal sanctions in Law Number 4 of 2009 concerning Mineral and Coal Mining and other provisions governing environmental protection in Indonesia. The main focus of the study is on the ambiguity of the "obstruction" element in Article 162 which has the potential to criminalize communities trying to protect their natural resources from mining exploitation. Through a normative legal approach, this study highlights the need to reform legal provisions to be clearer and fairer, and proposes a dialogue between communities and the government to ensure that community rights are protected. The results of the study indicate the importance of reviewing and definitively explaining ambiguous provisions in order to create legal certainty and justice for all parties involved.